Jet structure in pp and Pb-Pb collisions with the ALICE experiment - Busch, Oliver (Journal of physics. Conference Series, 2015)
We report results from the ALICE collaboration on jet production and jet properties in pp and Pb-Pb collisions at the LHC. The charged particle jet production cross-section and measurements of jet fragmentation and jet shape in pp collisions at = 7 TeV are presented. The results are confronted with simulations from Monte Carlo event generators. Measurements of charged particle jets in Pb-Pb collisions at = 2.76 TeV with resolution parameter R = 0.2 and R = 0.3 show a strong momentum dependent suppression in central relative to peripheral collisions. The analysis of the semi-inclusive distribution of charged particle jets recoiling from a high-pT trigger hadron allows an unbiased measurement of the jet structure for larger cone radii. No significant redistribution of the energy flow inside the jet cone is observed. Di-hadron correlations allow to assess jet structure at very low particle momenta. For 2 < pT,trig < 3 GeV/c and 1 < PT,assoc < 2 GeV/c, a strongly asymmetric near-side correlation, broader in Δη than Δϕ, is observed.
Gesehen am 23.10.2020